Non-Additive and Asymmetric Allelic Expression of p38 mapk in Hybrid Tilapia (Oreochromis niloticus ♀ × O. aureus ♂) - Zihui Liu; Binglin Chen; Zhiying Zou; Dayu Li; Jinglin Zhu; Jie Yu; Wei Xiao; Hong Yang (Animals, 2024)
Hybridization is a widely used breeding technique in fish species that enhances desirable traits in cultured species through heterosis. However, the mechanism by which hybrids alter gene expression to form heterosis remains unclear. In this study, a group of hybrid tilapia was used to elucidate heterosis through interspecies crossing. Specifically, p38 was analyzed to describe the regulation of gene expression variation in hybrid tilapia. Transcripts from the Nile tilapia allele were found to be significantly higher than those from the blue tilapia allele in hybrid individuals, indicating that the expression of p38 was dominated by Nile tilapia sub-genomic alleles. The study also found a compensatory interaction of cis- and trans-acting elements of the Nile tilapia and blue tilapia sub-genomes, inducing a non-additive expression of p38 in hybrids. Eight specific SNPs were identified in the p38 promoter regions of Nile tilapia and blue tilapia, and were found to be promoter differences leading to differences in gene expression efficiencies between parental alleles using a dual-luciferase reporter system. This study provides insights into the non-additive expression patterns of key functional genes in fish hybrids related to growth and immunity response.